1997
DOI: 10.1002/chem.19970030505
|View full text |Cite
|
Sign up to set email alerts
|

Nitridosilicates‐A Significant Extension of Silicate Chemistry

Abstract: Because of its low chemical reactivity Si3N4 has hardly been used as a starting material for the preparation of multinary silicon nitrides or nitridosilicates, but has gained increasing importance as a nonoxidic material for high‐performance applications. A novel synthetic approach is presented, which starts from silicon diimide (Si(NH)2) and makes available a large variety of novel nitridosilicates. The structures of these nitridosilicates represent a significant extension from those found in the family of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0
28

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 192 publications
(215 citation statements)
references
References 29 publications
4
175
0
28
Order By: Relevance
“…While the M-N bond lengths increase with increasing degree of condensation, the Si-N bond lengths tend to decrease with increasing degree of condensation, as has previously been observed by Schnick et al 12,84 This can also be observed from the data shown in Fig. 5a: the average Si-N distance is relatively large in for example Ca 4 SiN 4 (1.791 Å) with very low degree of condensation, while relatively small in SrSi 7 N 10 (1.731 Å) with a very high degree of condensation.…”
Section: Bond Lengthssupporting
confidence: 63%
“…While the M-N bond lengths increase with increasing degree of condensation, the Si-N bond lengths tend to decrease with increasing degree of condensation, as has previously been observed by Schnick et al 12,84 This can also be observed from the data shown in Fig. 5a: the average Si-N distance is relatively large in for example Ca 4 SiN 4 (1.791 Å) with very low degree of condensation, while relatively small in SrSi 7 N 10 (1.731 Å) with a very high degree of condensation.…”
Section: Bond Lengthssupporting
confidence: 63%
“…[9][10][11] ''Si(NH) 2 '' was obtained by ammonolysis of SiCl 4 in NH 3 (278 uC) followed by a thermal treatment at 600 uC under an atmosphere of NH 3 (see eqn. (1)).…”
Section: ''mentioning
confidence: 99%
“…[4] average value is higher than the sum of the corresponding ionic radii, due to the increased coordination of the nitrogen ion from N [2] to N [4] . This phenomenon is present in all the isotypic nitridosilicate and SiAlON compounds [3,4,19,21].…”
Section: (1) and T(2) T(1) Is Located On Wyckoff Position 2bmentioning
confidence: 87%